Assessment of dopamine receptor drd4 and drd5 mrna expression in peripheral blood lymphocytes of opioid & amphetamine type stimulant dependent Malay men undergoing methadone maintenance therapy - Jamil, Nur Khadijah Muhamad (2020)
In Malaysia and throughout the Asian region the mixed opioid and amphetamine type stimulants dependence is highly prevalent which has become a major health problem. Opioids and amphetamine-type stimulants (ATS) exert their effect by altering natural dopamine neurotransmission in the brain to achieve the ultimate goal of an extracellular hyper-dopamine state hence resulting drug reward effect. Dopamine actions are mediated by specific G proteins coupled receptors of two distinct families; D1-like receptor subtypes (D1 and D5) and the D2-like receptor subtypes (D2, D3, and D4). Evidence from previous studies has suggested that peripheral dopamine systems reflect the central dopamine system’s activity and pathology, especially in neuropsychiatric diseases. Studies have been carried out widely on central dopamine systems, while investigation of dopamine systems in various peripheral organs is still limited. It has been reported that peripheral blood lymphocytes express dopamine in peripheral systems. In this study, we investigated the difference in the mRNA expression of the dopamine receptors DRD4 and DRD5 in peripheral blood lymphocytes of ATS and opioid dependent Malay male subjects undergoing methadone maintenance treatment and healthy Malay male serving as control subjects. A total of 72 participants with 36 drugs dependent subjects and 36 control subjects were recruited from various parts of Kuala Terengganu, Terengganu according to inclusion and exclusion criteria. Demographic data including age, height weight, body mass index and blood pressure of all participants were recorded. A questionnaire form was given to the drug dependent subjects to assess their drug addiction status. Informed and written consent was obtained, and blood samples were collected. RNA was extracted from lymphocytes. The mRNA expression of the dopamine receptors DRD4 and DRD5 in peripheral blood lymphocytes was assessed by real-time PCR method. The demographic data of the subjects were calculated using Mann Whitney Test. The p-value 0.05 was used for the statistical significance. There was a significant difference between drug dependent subjects and control subjects for age and systolic blood pressure parameters while other parameters were not statistically significant. The DRD4 mRNA expression level is significantly reduced in lymphocytes of drug dependent subjects compared to control subjects (p=0.039). However, DRD5 mRNA expression level in lymphocytes of drug dependent subjects was not statistically significant (p=0.251). In conclusion, drug dependent subjects on mixed opioid and ATS dependence undergoing methadone maintenance treatment may exhibit different patterns of dopamine receptors DRD4 and DRD5 mRNA expressions in the peripheral lymphocytes. Further studies are recommended to support the findings of the present study.